Report of the Mysore Tenancy Agricultural Land Laws Committee - Planning Commission (Planning Commission, 1957)
The Mysore Tenancy Agricultural Land Laws Committee (1957) examined tenancy practices in Mysore to propose comprehensive reforms. Key recommendations include establishing fixity of rent, security of tenure, regulated land resumption by landlords, tenant purchase rights, and landholding ceilings. The report emphasizes protecting tenants’ livelihoods, promoting equitable land distribution, and transitioning toward cooperative or personal cultivation. Comparative analyses of other states’ tenancy laws informed proposals, and extensive public consultation shaped the recommendations. The Committee advocated for government oversight in cases of mismanagement, fair compensation for land transfers, and robust administrative structures to enforce the new legal framework. Overall, the report seeks to balance tenant protections with landlord rights while enhancing agricultural productivity and socio-economic equity in Mysore.
Mysore
Mysore
Keywords: Mysore Tenancy; Agricultural Land Laws; Tenant Rights; Landlord Rights; Rent Fixity; Security of Tenure; Land Resumption; Tenant Purchase; Land Ceiling; Cooperative Farming; Legislative Reform